The seminar on Da‘wah in Kuala Lumpur in 1977 and the emergence of Hijab awareness in Indonesia - Alwi, Alwi; Setiawan, Agus; Sunjayadi, Achmad; Ramlan, Yunadi (International Islamic University Malaysia, 2023)
In the late 1970s, a new awareness of wearing hijab emerged in Indonesia, especially among Muslim students in public schools. Even though it was banned by the New Order government throughout the 1980s, hijab was finally permitted to be worn in public schools and its use continued to spread in Indonesia since then. One of the activists who was involved in the emergence of hijab awareness suggested that it arose after The Asian Muslim Youth Seminar on Da’wah that was held in Kuala Lumpur in February 1977. This seminar was attended by representatives of Muslim youth organisations from several Asian countries. Using thematic analysis approach via library research and interviews, this study explores the extent to which the seminar relates to the rise of hijab awareness in Indonesia in that period. Although the seminar was not the only factor driving the emergence of hijab awareness in Indonesia, this research found that there was a close and dynamic relationship between the two.